A phenomenographic investigation on the use of iPads among undergraduate art and design students. (8th January 2014) - Souleles, Nicos; Savva, Stefania; Watters, Hilary; Annesley, Angela; Bull, Ben
Abstract The increasingly widespread use of iPads in higher education (HE) brings to the forefront questions about the contribution of these computer tablets towards teaching and learning. However, there is a noticeable gap of research on the instructional potential of iPads in HE. This paper describes the first stage of a research project on the use of iPads in undergraduate art and design disciplines, and is a collaboration between the research lab "Networked Learning Technologies in Art and Design" at Cyprus University of Technology, and the "Centre for Pedagogic Research" at Falmouth University in England. The participants from both institutions provided a student‐centred perspective, and the qualitative analysis (phenomenography) revealed varied perceptions. Based on the findings of this project, the implication is that there are a number of challenges and obstacles in embedding the use of iPads in art and design education. Further research in the second stage of this collaborative research will investigate the views and motivations of art and design faculty. A video abstract of this article can be viewed at https://www.youtube.com/watch?v=ZBXnuVJ8eBY